Characterization of Tri-Phasic Edible Films from Chitosan, Guar Gum, and Whey Protein Isolate Loaded with Plant-Based Antimicrobial Compounds. Issue 3 (11th February 2019) - Dhumal, Chanda Vilas; Pal, Kunal; Sarkar, Preetam
ABSTRACT: Essential oil containing tri-phasic films of chitosan, guar gum, and whey protein isolate were prepared. Eugenol, carvacrol, and citral were used as the oil phase, either alone or in combination. The addition of essential oils decreased the water vapor transmission rate and tensile strength of the films. CLSM confirmed the presence of essential oil droplets within the biopolymer matrix. XRD analysis indicated that the addition of essential oils altered biopolymer interactions. FTIR analysis suggested alterations within whey protein structure in the presence of essential oils. The essential oil containing films showed good antimicrobial activity, suggesting potential application in food packaging.